EFFECTIVENESS OF HIGH SCHOOL BIOLOGY LEARNING DURING THE COVID-19 PANDEMIC IN MUARO JAMBI REGENCY - Jodion Siburian; Gusti Ayu Muthia; Nabila Alifa Pramani; Suryaningrum Suryaningrum; Erawati Sonia (Universitas Negeri Padang, 2022)
Teaching and learning activities are required online to reduce the spread of the corona virus. All subjects are transferred to online media, including biology which in its teaching requires practicum for student understanding. The purpose of this study was to determine the effectiveness of online biology learning during the Covid-19 pandemic for high school/ equivalent students in Muaro Jambi Regency. This study uses a quantitative model with a survey method. In this study, researchers only describe problems of learning and the media used for online learning. The implementation is done by collecting data, managing, and presenting the data objectively. In the research conducted, 36.8% of students answered in doubt and 27.3% did not agree in understanding biological material. This shows that the effectiveness of learning biology during the Covid-19 period is still not effective, because of the obstacles experienced by students, namely the media or learning methods provided by educators do not attract students' interest, learning is boring, and some students do not have adequate facilities for online learning. Giving a lot of assignments makes it difficult for students to understand biology learning.